APPLYING JANGOI FOLKLORE FROM PENYENGAT ISLAND ON ELT - Pradipta Agustina; Nana Raihana Askurny; Indah Pujiastuti (Universitas Pendidikan Ganesha, 2023)
Teaching Eenglish as a foreign language in Indonesia had been a challenge. In the national curriculum, there is an idea to insert sociocultural aspect of Indonesia in the form of folklore into English language teaching (ELT). The researchers saw that Kepulauan Riau (Kepri) has many cultural entities, one of them is folklore. This study is to promote Jangoi, a coastal folklore story which has been uttered from generation to generation in Kepri, specifically in Penyengat Island, as a material to teach English. The research questions of this study are; how Jangoi become ELT materials, how were the students’ performances upon Jangoi, and how English teachers’ opinion about Jangoi. This study used R and D (research and development), that consists of four steps, that are 1) analysis and consideration upon student needs and context, (2) design and development the purposive work lesson; (3) implementation step, implementing Jangoi story in ELT, and (4) Evaluation. The result of this study are, Jangoi is needed to be processed before applied in ELT, by practicing the three steps, that are transliteration, Indonesia-English translation, and Translation-Validation. Students’performance upon Jangoi was good, it could be viewed from sets of multiple choice test and essay questions, and English teachers pointed that Jangoi can be applied in ELT.